A Simple LC-MS/MS Method for Determination of Gentamicin in Human Plasma and Uncertainty Evaluation - Prihati, Dita Amalia; Nurrokhimah, Miftah; Fatimah, Nurul; Harjono, Sigit Sulistya; Nafiisah, Nur Hasna; Yuliani, Hanifah Ratna; Palgunadi, Tama Jahtra (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2026)
Gentamicin is an antibiotic with a narrow therapeutic index that necessitates therapeutic drug monitoring (TDM) to enhance efficacy and reduce toxicity. The goal of this study was to a simple, sensitive, and reliable LC-MS/MS method for measuring gentamicin in human plasma with a key novelty being the comprehensive assessment and documentation of measurement uncertainty integrated into the method validation process. The method used a Sciex QQQ 4500 LC-MS/MS system equipped with a C18 column, 5 x 20 mm, 4 µm Fusion-RP 80 Å, and operated in multiple reaction monitoring (MRM) mode, employing amikacin as the internal standard. Method validation was conducted following ICH M10 (2022) guidelines, encompassing parameters of selectivity, linearity, accuracy, precision, stability, dilution integrity, and carry-over. The calibration curve showed good linearity (r² = 0.990–0.996) over the range of 100–5000 ng/mL, with a lower limit of quantification (LLOQ) of 100 ng/mL. Across all concentration levels, accuracy (within ±15%; ±20% at LLOQ) and precision (≤15% CV; ≤20% at LLOQ) met the acceptance criteria. Short term stability experiments indicated that the samples maintained enough rigidity for various handling and storage method. We used EURACHEM and JCGM GUM guidelines to figure out the measurement uncertainty. The standard error of the slope (SEm) was the biggest factor. The total uncertainty was found to be 0.27 ng/mL, which means that the expanded uncertainty is ±0.55 ng/mL with 95% confidence. The validated method is strong and dependable, which makes it good for use in clinical settings for gentamicin TDM.